COMPARATIVE FINANCIAL PERFORMANCE OF REGIONAL DEVELOPMENT BANKS (BPDS) AND THE BANKING INDUSTRY IN INDONESIA - Roberto Akyuwen; Y. Sri Susilo; Raden Kusumawijaya (Journal of Applied Economics in Developing Countries, 2019)
Regional development banks (BPDs) are essentially designed as regional development agents and dedicated to create employment, alleviate poverty, and reduce disparity at the regional level. In the context of banking operations, BPDs are expected to become regional champions in their respective regions. This expectation can be met only if BPDs are able to compete with the other types of commercial banks and non-bank financial institutions, including rural banks and financial technology companies. This research was aimed at comparing the financial performance of BPDs and the banking industry in Indonesia. A descriptive approach was used to analyze the current secondary data gathered from the Indonesia Financial Services Authority (OJK). The results have shown that, in general, the average financial performance of all BPDs was lower than that of the banking industry. However, the group of smallest BPDs had a higher growth compared to the banking industry.Keywords: Banking Industry, Financial Performance, Regional Development Banks.